A comparative study for the extraction methods and solvent selection for isolation, quantitative estimation and validation of ursolic acid in the leaves of Lantana camara by HPTLC method - Mahvish Jamal; Mohd Amir; Zunab Ali; Mohd Mujeeb (SpringerOpen, 2018)
To select the best organic solvent and ideal extraction technique for isolation and quantitative estimation of ursolic acid from the leaves of Lantana camara (L. camara) by high performance thin layer chromatography (HPTLC). A sensitive, fast and reproducible HPTLC method was developed and validated for estimation of ursolic acid from the leaves of L. camara. Different leaves extracts of L. camara were prepared through different extraction methods (maceration, reflux, soxhlet and ultrasound assisted extraction technique) by using four different solvents of varying polarity such as ethanol, methanol, acetone and chloroform. The maximum % extract yield was obtained in methanol, so we select methonolic extract for HPTLC evaluation. The calibration plot of standard ursolic acid with respect to peak area showed an tremendous linear relationship in the concentration range of 1000-4000 ng/spot with a correlation coefficient r2 = 0.994. The separation was completed on precoated silica gel aluminium plates 60F254 using Toluene: Acetone: Formic Acid (7.8:2.2:0.15) as mobile phase which gives a compact spot of ursolic acid (Rf value 0.49). For the proposed method (Limit of Detection) LOD (561.85 ng/spot), (Limit of Quantification) LOQ (1702.58 ng/spt), recovery of drug (99.02-101.43%) and precision (0.4303-2.1576% RSD) was found to be satisfactory. It can be concluded on the basis of HPTLC results that methanol was found to be the best solvent and Soxhlet was found to be an ideal extraction technique for the isolation of ursolic acid from L. camara leaves for routine analysis. Keywords: Lantana camara, Ursolic acid, HPTLC, Extraction techniques